2014
DOI: 10.1038/ncomms4215
|View full text |Cite
|
Sign up to set email alerts
|

Probing backbone hydrogen bonding in PDZ/ligand interactions by protein amide-to-ester mutations

Abstract: PDZ domains are scaffolding modules in protein-protein interactions that mediate numerous physiological functions by interacting canonically with the C-terminus or non-canonically with an internal motif of protein ligands. A conserved carboxylate-binding site in the PDZ domain facilitates binding via backbone hydrogen bonds; however, little is known about the role of these hydrogen bonds due to experimental challenges with backbone mutations. Here we address this interaction by generating semisynthetic PDZ dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 52 publications
4
64
0
Order By: Relevance
“…We designed and synthesized five different amide-to-ester mutants of PSD-95 PDZ2, L170λ, G171γ, F172φ, I174ι and G176γ as described [21] (see Powers et al [24] for nomenclature of amide-to-ester mutations). In general, such backbone mutations remove a hydrogen bond formed by the NH of the amide and destabilize the hydrogen bond formed by the amide carbonyl oxygen [3], [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed and synthesized five different amide-to-ester mutants of PSD-95 PDZ2, L170λ, G171γ, F172φ, I174ι and G176γ as described [21] (see Powers et al [24] for nomenclature of amide-to-ester mutations). In general, such backbone mutations remove a hydrogen bond formed by the NH of the amide and destabilize the hydrogen bond formed by the amide carbonyl oxygen [3], [24].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the pseudo wild type in the folding experiments in this paper is the double mutant of PSD-95 PDZ2, V178C/Y190W. Semisynthesis of the PSD-95 PDZ2 V178C/Y190W amide-to-ester mutants was performed as previously described [21].…”
Section: Methodsmentioning
confidence: 99%
“…1A and B). [18][19][20] Truncation studies of peptide ligands targeting PSD-95 have shown that pentapeptides display affinities similar to longer peptides, while tetra-and tripeptides show a stepwise reduction in affinity. 15 pentapeptides have subsequently been derivatized into dimeric inhibitors with nanomolar potency.…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal carboxylic acid of the peptide ligand is crucial for binding 17 and is accommodated by the conserved PDZ 'GLGF' loop. 18 Peptides binding to PDZ domains form an anti-parallel β-sheet with the PDZ βB strand via amide backbone hydrogen bonds. 14,18,19 Structure-activity relationship (SAR) investigations of both peptide and protein backbone have revealed that not all amide atoms of the peptide engage directly with the PDZ domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation